PEMIKIRAN ADIWARMAN AZWAR KARIM TERHADAP KONSEP ECONOMIC VALUE OF TIME (2010-2018) DALAM PERSPEKTIF HUKUM EKONOMI SYARIAH - Elisafitri, Risma Okta; Junaidi, Heri; Afriansyah, Syafran (Program Studi Muamalah Fakultas Syariah dan Hukum, 2020)
The research entitled Adiwarman Azwar Karim's Thought Against the Concept of Economic Value of Time (2010-2018) in the Perspective of Islamic Economic Law, this departs from the main problem related to the difference in the value of money and time. Therefore, Adiwarman Azwar Karim offers the concept of Economic Value Of Time. This research is a library research (Library Research) with the primary source of books by Adiwarman Azwar Karim, namely Islamic Microeconomics (2010), Islamic Bank Islamic Fiqh Analysis and Finance (2016). Secondary sources are studied from books other than the character's original books, journals, websites, articles. In data collection, the steps taken were to collect Primary Data Sources and Secondary Data Sources then classify existing data, then arrange them systematically and become a conceptual framework for how Economic Value of Time in the Islamic economy with Adiwarman Azwar Karim's thought, then draw conclusions. The results of the study concluded that: (1) The concept of Economic Value of Time according to Adiwarman Azwar Karim is a concept where time has economic value, not money which has time value. The concept of Economic Value of Time Adiwarman Karim is a rebuttal to the Time Value of Money system, where the concept of Economic Value of Time is based on a standard calculation of money with no additional value. Meanwhile, Time Value of Money directs people to the value of profit from money to money with additional value (usury). (2) In the perspective of Islamic Economic Law, the concept of Time Value of Money is more acceptable than the concept of Time Value of Money because the concept of Time Value of Money, the calculation system uses a ratio (profit sharing), while the calculation system of Time Value of Money uses interest. The purpose of Islamic law is based on maintaining five important things based on a priority scale, namely: (1) preserving religion, (2) preserving the soul, (3) preserving reason, (4) preserving offspring and (5) maintaining property. Islamic law contains eternal fitriyah values ​​based on solid principles, which will not change and will not be changed. Keywords: Adiwarman Azwar Karim, Economic Value of Time, Money